The Effect of Financial Compensation and Non-Financial Compensation on Employee Performance with Motivation as an Intervening Variable in Yogyakarta Startup Companies - Dodi Setiawan Riatmaja; Sigit Wibawanto (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2022)
The purpose of this study was to determine the effect of compensation on the performance of employees of startup companies in Yogyakarta with motivation as an intervening variable; to determine the effect of financial compensation on employee performance, to determine the effect of non-financial compensation on employee performance. This research was conducted by taking startup employees in Yogyakarta randomly as many as 73 employees. The calculation technique used in this study is the Multiple Linear Regression Analysis model and path analysis. Based on the analysis results indicate that there is a significant influence between financial compensation and non-financial compensation on employee performance; there is a significant influence between financial compensation and non-financial compensation on employee performance with notibvasi as an intervening variable.